IMPROVING STUDENTS’ READING COMPREHENSION OF VIII GRADE AT SMK NEGERI 1 TULIN ONSOI THROUGH RETELLING STORY - Mariana Mariana (Universitas Madako Tolitoli, 2020)
The objective of this research is to find out whether Retelling Story can improve students’ reading comprehension of X grade at SMK Negeri 1 Tulin Onsoi or not. This research is pre experimental research design consist of one group pre-test and post-test. The Population of this research are the eight grade of SMK Negeri 1 Tulin Onsoi in 2016/2017 academic year. The sample of this research is selected by using purposive sampling technique and the selected class is VIIIA consisted of 30 students. In collecting the data, the researcher conduct test covered pre and post test. The researcher analized the data statically. The result of the test showed that the students’ mean score in posttest 77.60 is higher than pretest 39.47 To know the significant difference between pretest and posttest, the researcher compared the value of t-counted and t-table by applying 0.05 level of significance for two-tailed test with 29 degree of freedom (30-1=29),the researcher found that the tcount is higher than ttable and the hypothesis of this research is accepted. The researcher concluded that using Retelling Story can improve students’ reading comprehension at eight grade of SMK Negeri 1 Tulin OnsoiKeywords: Reading comprehension, Retelling story